THE PROFILES OF METACOGNITIVE READING STRATEGIES OF SUCCESSFUL AND UNSUCCESSFUL EFL LEARNERS OF SENIOR HIGH SCHOOL - Muhammad Reffyal; Abidin Pammu; Sukmawaty Sukmawaty (JURNAL ILMU BUDAYA, 2018)
The ability to read in English as a foreign language is very important for senior high school because it will affect their productive skills such as writing and speaking. The objective of this research was to present the profiles of metacognitive reading strategies of successful and unsuccessful EFL learners of high school at SMA Negeri 1 Pamboang. The address of reading strategies is expected to provide useful information both for students and teachers secondary school. At least, the information about strategies can improve the quality of education especially in teaching reading as a core subject. The current study reports an investigation of EFL learners profiles of metacognitive reading strategies in Indonesian context. This exploratory paradigm was an attempt to reveal what level of metacognitive awareness of both successful and unsuccessful learners at the senior high school level. The study was carried out at SMA Negeri 1 Pamboang, Majene Regency and employed quantitative and qualitative methods. Using purposive sampling method, seventy-two (72) EFL learners filled in the MARSI questionnaire (Metacognitive Awareness Reading Strategy Inventory) by Mokhtari & Reichard (2002) to deal with the metacognitive part. 20 samples from seventy-two participants were selected to participate in interview session. The former employed statistical tool (SPSS 22) to reveal the level of learners’ metacognitive awareness. The statistical analysis indicated high level of metacognitive of awareness in all sub-scales (Global Strategy, M=3.59, SD=0.56, Support Strategy, M=3.51, SD=0.77, Problem Solving Strategy, M=3.77, SD=0.65) for the successful group. The unsuccessful group, on the other hand, indicated medium level on both Global and Support Strategy (M=3.16, SD=0.60, M=3.06, SD=0.49) with the exception of Problem Solving Strategy with a high level of awareness (M=3.58, SD=0.55). Interviews showed that many students, especially unsuccessful learners, have a clear purpose when reading but when they did not understand they choose to discuss with friends. This finding warranted the need for the design of strategy training with the focus on strategy consolidation to make these learners employ these existing strategies in more productive and efficient manner.